PEMILIHAN BAHASA ETNIK BUGIS DALAM RANAH KELUARGA BERDASARKAN HUBUNGAN PERAN DAN KATEGORI PENDIDIKAN DI KABUPATEN DONGGALA - NFN Tamrin (Multilingual, 2016)
Language choice is a common phenomena that occurs in multilingual societies. Indonesia people consist of various cultures, races, and ethnics and also various of languages which they used to communicated between their families and their societies. This research wants to find out the language choice of the Buginese ethnic infamily domain based on roles relation and education category in Donggala Regency. This research aims to (1)described the pattern language choice of the Buginese ethnic in family domain based on eduaction categoryand roles relation in Donggala Regency and (2) analyzed the factors language choice of the Buginense ethnicin family domain based on roles relation and education category in Donggala Regency. This research useda sociolinguistic approach method by quiestionnaire, interview, observation, recording technique, and thenanalyzed the data based on the percentage of language choice of the Buginese ethnic in family domain. Theresults showed that the Buginese ethnic in Donggala regency still dominant choose Bugis as a means ofcommunication in family domain based on roles relation and education category (82%), which is about 8%used Indonesian, 7% choose to mix Bugis and Indonesian, and only 3% used another languge, that is locallanguage, Dampal and Mandar.